Cricket Helps to Improve Fitness of Elementary School Children: Literature Review - I Putu Herry Widhi Andika; I Wayan Artanayasa; Made Agus Dharmadi; Ketut Sudiana (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2024)
Cricket is a team sport played by 6-11 people. In playing all body parts are involved. So that all body parts become active in moving. The purpose of this study was to examine the physical condition of elementary school children in cricket can improve their fitness. This study includes literature review research. The data needed are scientific articles that have been published in various journals. The article search was carried out using the Google Scholar fast search engine. The keywords entered were cricket and started from publications in 2020 to 2024. The articles used as primary data were articles published in national journals, at least nationally accredited, and reputable international journals. Based on the screening results, eight articles were obtained that were eligible for review. The results of the study showed that cricket is very relevant to improve the fitness of elementary school children. It is recommended for teachers and sports coaches to try using cricket games before or after carrying out core sports activities as a variation in teaching.